Effect of Feed Rate on Shear Strength and Macrostructure of Friction Stir Welding Dissimilar High Density Polyethylene-Polypropylene Joint - Ardiyansyah, Nur; Suwanda, Totok; Yudha, Fitroh Anugrah Kusuma; Purnama, Adi (Politeknik Negeri Lhokseumawe, 2024)
The connection of dissimilar materials is complicated, too. This connection is due to differences in physical and mechanical properties, but with the development of technology, dissimilar materials can be joined using solid-state welding methods. Dissimilar joints can produce a good combination of structure and mechanical properties. One of them is friction stir welding, which is used to connect sheet materials. The welding process of this research uses a conventional vertical milling machine. This study aims to determine the maximum shear strength and welding defects against variations in the feed rate of lap joints dissimilar high-density polyethylene with polypropylene. The machining parameters used in this experiment were 4 mm pin tool diameter, 2360 rpm rotation speed, 9 mm/min, 12 mm/min, and 16 mm/min feed rate. The results showed that the highest shear strength was obtained using the 12 mm/min feed rate variation of 3.11 N/mm. It can be seen in the macrostructure that the incomplete defects produced are less than the other welding process variations.